Traceability of pork - advantages, benefits, monitoring - Elena Petrescu Irina (Ekonomika Poljoprivrede (1979), 2010)
Globalization of trade expands distribution of products and services worldwide, making it more difficult to control the content and quality. To prevent "food terrorism it is necessary to know the evolution of animals from birth to end of life. As long as an animal remains in the same group is easily identified by group ID. But once it leaves the farm, things become more complicated and traceability implementation must take into account many factors. For analysis, the firm needs information about vaccination, food, medication and supervision.